The Relationship Between Maternal Knowledge Level And Feeding Practices With Dietary Patterns In Stunted Children - Syafira Dwi Ananta; Ilya Krisnana; Wahyuni Tri Lestari (Jurnal EduHealth, 2023)
Introduction: Stunting in children becomes a problem as a result of several factors including the level of mother's knowledge, feeding rules, and eating patterns. Data from Basic Health Research (Riskesdas) for 2022, the stunting rate in Indonesia is 21.6% (Ministry of Health RI, 2022). While the target standard for the National Medium-Term Development Plan (RPJMN) is 19% in 2024. This study aims to analyze the relationship between the level of mother's knowledge and feeding rules with eating patterns in stunted children. Methods: This research employed a correlational study design and a cross-sectional approach. The sample consisted of 87 respondents selected using a simple random sampling technique. This study’s independent variables were maternal knowledge and feeding rules, and the dependent variable was dietary habits. The data was collected using a maternal knowledge level questionnaire, a fundamental feeding rules questionnaire, and a children’s feeding questionnaire (CFQ), which was subsequently analyzed using Spearman’s Rho with a significance level of α=0,05. Results: The bivariate analysis findings demonstrated a significant correlation between maternal knowledge and dietary habits patterns (p=0.000) (r=0.372). In addition, there was a significant correlation between feeding rules and dietary habits (p=0.000) (r=0.424). Conclusion: The level of maternal knowledge and feeding rules were related to children’s diet patterns. The level of maternal knowledge and feeding rules were factors associated with the dietary habits of stunted children; thus, increasing maternal knowledge and feeding rules would improve the diet patterns.